Indonesian-based Islamic Religious Education by KH. Soleh Darat and its Relevance to Islamic Education Based on Religious Moderation - Zulaikhah, Siti; Munir; Ibrahim, Duski; Karoma (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This study aims to describe and analyze the thoughts of Kiai Soleh Darat Al-Samarani regarding Islamic education, focusing on three main aspects: (1) the concept of education, including its goals, foundations, the roles of educators and students, and the curriculum; (2) the distinctive characteristics of Islamic education in Indonesia introduced by Kiai Soleh Darat; and (3) the relevance of this approach to Islamic education with a perspective on religious moderation. The research employs sociological, historical, and philosophical approaches, with primary data sources consisting of Kiai Soleh Darat's works such as “Al-Mursyid al-Wazīz fī ‘Ilmi al-Qur'ān al-‘Azīz” and “Majmū al-Syarī’at al-Kāfiyat lī al-‘Awām.” The findings indicate that Kiai Soleh Darat developed an inclusive and integrative approach to Islamic education, respecting local customs while emphasizing the importance of sincere intentions in seeking knowledge. His teaching materials encompass all aspects of Islamic teachings and are relevant to the social context of his time. Kiai Soleh Darat played a significant role in contextualizing Islamic teachings with societal issues, instilling values of nationalism and tolerance, and opposing violence through education. His works have become important references for students and contributed to Indonesia's struggle for independence.